Structural Transformation of Agriculture and Poverty in Indonesia - Fitria Ardiansyah; Herman Cahyo Diartho; Endah Kurnia Lestari (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2020)
The trend of modern development in some countries is the decline in the contribution of the agricultural sector to GDP (gross domestic product), as a consequence of the increased contribution of the non-agricultural sector. So the development strategy that is often applied is to increase the role of the modern sector (industry and services) that have a high level of productivity. The agricultural sector, which has low productivity, often escapes the development strategy, even though the agricultural sector is a place to make a living for some poor people who are in rural areas. This study aims to analyze the effect of economic structural transformation on poverty in Indonesia. The type of data used in this study is quantitative data, in the form of time series data between 1980-2017 obtained from World Bank publications, the World Income Inequality Database, and the Central Statistics Agency. Analysis of the data used is to use VECM estimation to see the short-term relationship and the long-term relationship of each variable. The estimation results of the Vector Error Correction Model (VECM) concluded that in the long run, the agricultural sector has a negative and significant relationship to poverty, while the industrial and service sectors do not have a significant effect on poverty in Indonesia. Per capita income has a positive relationship with poverty in Indonesia. Based on the explanation, it concludes that the policy that must be implemented to overcome the problem of poverty is to develop the agricultural sector.